Reincentivizing Work - Hans Thulesius; Birgitta E. Grahn (Grounded Theory Review: An International Journal)
Work capacity has a weak correlation to disease concepts, which are insufficient to explain sick leave behavior. With data mainly from Sweden, a welfare state with high sickness absence rates, our aim was to develop an explanatory theory of work and sick leave. We used classic grounded theory for analyzing data from 130 individual interviews of people working or on sick leave, physicians, social security officers, and literature. More than 60,000 words and hundreds of typed and handwritten memos were the basis for the writing up of the theory. In this paper we present a theory of “reincentivizing work”. To understand incentives we define work disability as hurt work drivers or work traps. Work drivers are specified as work capacities + work motivators, monetary and non-monetary. Incentives are recognized when hurt work drivers are assessed and traps identified. Reincentivizing is done by repairing hurt work drivers and releasing from traps. In our theory of reincentivizing work, hurt work drivers and traps are recognized and then repaired and released. The theory may add to social psychological research on work and sickness absence, and possibly inform future changes in sick leave policies.